MANAJEMEN PEMBERDAYAAN EKONOMI BERBASIS PESANTREN (STUDI KASUS DI PONDOK PESANTREN AL – IKHWANIYYAH GUMUKMAS) - Uliyatul Mu’awwanah; Muhammad Syarofi; Muhsin Muhsin (Program Studi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, IAIN Fattahul Muluk Papua, 2021)
Islamic boarding school (Pondok Pesantren) is the oldest religious institution in Indonesia. Its existence on education by spreading knowledge that can create Muslim scholars as new generations. Islamic boarding school has identical function as a place to study religion that it is a narrowing claim with the fact, Islamic boarding school can give more contributions to build society or economy. Along the line with the spread of various issues on global economic, such as unemployment due to limited employment opportunities, so that it impacts on increasing of poverty. This research focuses on how to manage economic empowerment along with the financial management system at Pondok Pesantren Al-Ikhwaniyyah Gumukmas Jember. This research purpose is to find out the aspects mentioned in the research focus. The research method applied is the qualitative method with a case study approach. The result of this research shows that Pesantren Al-Ikhwaniyyah has been able to implement economic empowerment management along with its financial administration starts from planning, organizing, implementing, and supervising. However, the system of financial administration needs to be improved more by inviting external auditors to maintain financial governance.